Triple and quadruple spontaneous cervical artery dissection: presenting characteristics and long-term outcome. Issue 2 (31st October 2008) - Arnold, M; De Marchis, G M; Stapf, C; Baumgartner, R W; Nedeltchev, K; Buffon, F; Galimanis, A; Sarikaya, H; Mattle, H P; Bousser, M G
Abstract : Background: Spontaneous cervicocephalic artery dissection (sCAD) of more than two cervical arteries is rare. Patients and methods: Vascular and potential sCAD risk factors, triggering events, clinical and neuroimaging findings, and outcome of patients with multiple sCAD were studied. Patients were drawn from prospective hospital-based sCAD registries. Results: Of 740 consecutive patients with sCAD, 11 (1.5%) had three, and one had four (0.1%) sCAD. Eight of these 12 patients were women. One patient had additional dissections of the celiac trunk and hepatic artery. Vascular risk factors included hypertension (n = 1), hypercholesterolaemia (n = 6), current smoking (n = 5) and migraine (n = 6). No patient had a family history of sCAD, fibromuscular dysplasia (FMD) or connective tissue disease. SCAD was preceded by a minor trauma in five and infection in four patients. Clinical manifestations included ischaemic stroke (n = 8), transient ischaemic attack (n = 3), headache (n = 9), neck pain (n = 4), Horner syndrome (n = 5), pulsatile tinnitus (n = 2) and dysgeusia (n = 1). Brain MRI revealed ischaemic infarcts that affected one vessel territory in seven and two territories in two patients. The 3-month outcome was favourable (modified Rankin scale score 0–1) in 10 patients (83%). No new recurrent stroke or sCAD occurred during a mean follow-up of 50 (SD 29) months. Conclusion: Multiple sCAD occurred preferentially in women and caused clinical symptoms and signs mainly in one vascular territory. In none of the patients was FMD or any other underlying arteriopathy apparent. The majority of multiple sCAD was preceded by a minor trauma or infection. Clinical outcome was favourable in most patients, and long-term prognosis benign. The data suggest that transient vasculopathy may be a major mechanism for multiple sCAD.